In Pursuit of the World’s Best Steak – Advanced Robotics and X-ray Technology to Transform an Industry - Ruberg, Christian (Journal of Applied Business and Economics, 2021)
Australia strives to be the world’s preferred supplier of premium red meat, but it is challenged by having a high cost structure. In response, Meat & Livestock Australia (MLA), the processing industry, and key technology providers have spent the last 14 years developing and implementing robotic automation supported by advanced real time sensing technology such as x-ray imaging. This paper outlines the investment strategy behind collaborating with the world’s leading companies, and successfully integrating: meat science, industrial robotics, medical imaging, and airline baggage inspection security systems, into Australian beef and sheep meat supply chains. These world-first systems, that were initially implemented in lamb processing, feature: robotic cutting, dual energy x-ray, machine vision, laser sensing, and carcase traceability for producer feedback. The beef processing sector is now set to benefit from the learnings and technical progress demonstrated in lamb processing. These innovations have moved Australia into first place for advanced red meat processing automation and have delivered in some cases an under 2-year capital payback with an up to 25% improvement in boning room productivity.